2010
DOI: 10.1111/j.1708-8305.2010.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Illness in French Travelers to Senegal: Prospective Cohort Follow‐up and Sentinel Surveillance Data

Abstract: In this study, we suggest the complementary nature of using cohort surveys and sentinel surveillance data. Effective protection of skin from arthropod bites and sun exposure should result in significantly reduced travel-associated diseases in Senegal. Travelers to Senegal should be informed that diarrhea is extremely common despite preventive measures, but it is mild and transitory and should not lead to the disruption of malaria chemoprophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
1
16
0
2
Order By: Relevance
“…Compliance with these measures and, therefore, the effectiveness of the recommendations has been found to be poor [6,20]. The high risk of TD found in our study is comparable with earlier prospective studies, which have found attack rates to vary between 25% and 57% [4,9,11,21,22]. …”
Section: Discussionsupporting
confidence: 71%
“…Compliance with these measures and, therefore, the effectiveness of the recommendations has been found to be poor [6,20]. The high risk of TD found in our study is comparable with earlier prospective studies, which have found attack rates to vary between 25% and 57% [4,9,11,21,22]. …”
Section: Discussionsupporting
confidence: 71%
“…tourists or conference attendees) and nationality of travellers included. During the past 40 years, seven additional studies, 915 six of which were published since 2006, have provided information that may lead to a more generalizable and accurate estimate of the proportion of international travellers that acquire a travel-related illness.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,10,12,13,15 Travellers who attend a pre-travel consultation receive education on mitigation of health risks during travel and prevention of infectious diseases, including personal protective measures, chemoprophylaxis, and vaccination. 16 Attendance at a pre-travel consultation may result in decreased illness if clinicians provide travellers with prevention information 17 and the travellers adhere to these preventive measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations